Manajemen Sistem Informasi Kesehatan di Dinas Kesehatan: Suatu Tinjauan Literatur Tentang Tantangan Dan Strategi Implementasi - Rista, Indriana; Irma, Eka; Sari, Dea; Hartono, Budi; Daud, Alfani Ghutsa (Universitas Pahlawan Tuanku Tambusai, 2025)
Introduction: The Indonesian Health One Data Application (ASIK) is a government initiative aimed at achieving national health data integration. However, at the District Health Office level, the implementation of ASIK faces significant challenges such as limited human resources, inadequate ICT infrastructure, and budget efficiency constraints. Methods: This journal uses a literature review method, with data obtained from the Google Scholar database covering publications from 2020 to 2025, resulting in seven selected references. Results and Discussion: The study reveals that the implementation of the Health Information System at District Health Offices faces challenges related to inconsistent data quality, limited human resource skills, inadequate ICT infrastructure, and fragmented, non-integrated systems. Other issues include low motivation and weak supervision of data managers, poor user-friendly system design, and unequal internet access in remote areas. Recommended strategies include online training, coordination through Zoom meetings, the development of lightweight web-based systems, planned infrastructure funding, and ongoing technical assistance from central authorities. Conclusion and Recommendations: This study concludes that the implementation of Health Information Systems at District Health Offices is still hindered by issues of data quality, limited human resources, lack of system integration, and uneven infrastructure. Suggested strategies include online training, virtual coordination, user-friendly system development, and supportive national policies. Health Offices are encouraged to develop standardized data management SOPs, strengthen HR training, and optimize the use of digital technologies to improve efficiency and data integration toward achieving Indonesia's Health One Data vision.